The Capsid and Tegument of the Alphaherpesviruses Are Linked by an Interaction between the UL25 and VP1/2 Proteins - Coller, Kelly Elizabeth (American Society for Microbiology (ASM), 2007)
How alphaherpesvirus capsids acquire tegument proteins remains a key question in viral assembly. Using pseudorabies virus (PRV), we have previously shown that the 62 carboxy-terminal amino acids of the VP1/2 large tegument protein are essential for viral propagation and when transiently expressed as a fusion to green fluorescent protein relocalize to nuclear capsid assemblons following viral infection. Here, we show that localization of the VP1/2 capsid-binding domain (VP1/2cbd) into assemblons is conserved in herpes simplex virus type 1 (HSV-1) and that this recruitment is specifically on capsids. Using a mutant virus screen, we find that the protein product of the UL25 gene is essential for VP1/2cbd association with capsids. An interaction between UL25 and VP1/2 was corroborated by coimmunoprecipitation from cells transiently expressing either HSV-1 or PRV proteins. Taken together, these findings suggest that the essential function of the VP1/2 carboxy terminus is to anchor the VP1/2 tegument protein to capsids. Furthermore, UL25 encodes a multifunctional capsid protein involved in not only encapsidation, as previously described, but also tegumentation.